Flow and clogging behavior of a mixture of particles in a silo - Bhure, Sukhada C.; Doshi, Pankaj; Orpe, Ashish V. (Physics of Fluids, 2024)
We investigated the clogging behavior observed during the flow of aspherical particles from a silo in the presence of spherical particles of different sizes and proportions using flow visualization experiments and discrete element method simulations. The size of the avalanche, essentially the tendency of clogging, exhibits non-monotonic dependence on the spherical particle volume fraction. For small enough content of spherical particles, the clogging tendency intensifies, whereas it reduces rapidly for high enough spherical particle fractions, with a minimum in between. The non-monotonic behavior is observed to persist over for different spherical particle sizes. The overall behavior is shown to arise due to competing effects between the localized total particle fraction influencing avalanche strength and mean size of the particles exiting the silo, influencing the probability of arch formation.